Changes in the number and capacity of hotels in Poland - Matczak, Andrzej (Turyzm/Tourism, 2017)
The author’s aim is to identify changes in the rate, intensity and direction of hotel development, as well as their number, type and capacity of in Poland, by category and province in 1990-2015. The objective is to define the influence of both tourism attractiveness and economic development factors (GNP, total capital expenditure, the value of gross fixed capital formation – GFCF) on the changing number of hotel rooms. The identification was based on commonly available materials provided by the Local Data Base (LDB) of the Central Statistical Office (CSO), as well as from statistical year books concerning the tourism sector. The article presents methods for analysing indices, as well as correlation and graphic presentation (graphs, maps). From 1990 to 2015, there was a rapid increase in the number and capacity of hotels in Poland (4.5 times), especially in higher (5* and 4*) and medium standard (3*) hotels. That increase was significantly diversified regionally and strongly depended on the tourism attractiveness and socioeconomic development of provinces.